The Hamlet of ʽAin el-Gedida in Dakhla Oasis: A Late Roman Epoikion? - Aravecchia, Nicola.
This article discusses archaeological and documentary evidence from the late Roman settlement of ʽAin el-Gedida (located in the Dakhla Oasis of Upper Egypt), with a particular focus on the site’s likely identification as an epoikion, i.e., a small rural center associated with the management of a large agricultural estate. ʽAin el-Gedida was first excavated by an Egyptian mission in 1993–1995 and immediately raised interest among scholars working in the oasis, with the site being preliminarily identified either as a rural village or a monastic settlement. More recent excavations and study seasons, conducted (from 2006 to 2010) by a Columbia University (then New York University) mission directed by Roger Bagnall, has allowed investigators to gather a substantial amount of new data. This evidence, published in 2018 and more recently in 2020, supports the likely identification of ʽAin el-Gedida as an epoikion over other types of settlements. In this article, the data from ʽAin el-Gedida are discussed in light of what is known from documentary sources about epoikia, as well as modern Egyptian ezab. Worthy of note is that not many other agricultural hamlets of a comparable size have been extensively excavated and published thus far. It is also remarkable that, while written evidence on epoikia abounds, the site of ʽAin el-Gedida may provide the first available archaeological evidence for this type of settlement; therefore, it may offer new and useful data on the layout and organization of epoikia in late antique Egypt.